La formation et l'emploi des diplômes en beaux-arts, en humanités et en sciences sociales au Canada - Farine, Avigdor; Knowles, Ron (Canadian Journal of Higher Education, 1976)
Higher education in Canada has experienced a large expansion in the last decade. The student population grew by 15 percent per year, which raised the proportion of the 18-24 year old age group participating in post-secondary education from 10.2 percent in 1960-1961 tol 7.4 percent for men and from 3.3 percent to 9.8 percent for women. During the same period, the support allocated to this sector of education increased by 20 percent per year. In Quebec, for example, while the P.N.B. increased by 8.6 per year and the number of students grew by 13 percent, the operating costs of higher education grew by 23.5 percent per year.1 The cost of this education and the difficult economic situation lead us to review the question of development and role. In this article, we shall limit ourselves to degrees in fine arts, humanities, and social sciences in Canada, having dealt elsewhere with the other major categories of highly qualified manpower (MHQ)2. The post-census inquiry data on MHQ prepared in 1973 by Statistics Canada for the Ministry of State for science and technology serves as the basis for our study.